Genome-wide analysis of DNA methylation identifies novel differentially methylated regions associated with lipid accumulation improved by ethanol extracts of Allium tubersosum and Capsella bursa-pastoris in a cell model. - Moonju Hong; Jin-Taek Hwang; Eun Ju Shin; Haeng Jeon Hur; Keunsoo Kang; Hyo-Kyoung Choi; Min-Yu Chung; Sangwon Chung; Mi Jeong Sung; Jae-Ho Park (PLoS ONE, 2019)
Hepatic steatosis is the most common chronic liver disease in Western countries. Both genetic and environmental factors are known as causes of the disease although their underlying mechanisms have not been fully understood. This study investigated the association of DNA methylation with oleic acid-induced hepatic steatosis. It also examined effects of food components on DNA methylation in hepatic steatosis. Genome-wide DNA methylation of oleic acid (OA)-induced lipid accumulation in vitro cell model was investigated using reduced representation bisulfite sequencing. Changes of DNA methylation were also analyzed after treatment with food components decreasing OA-induced lipid accumulation in the model. We identified total 81 regions that were hypermethylated by OA but hypomethylated by food components or vice versa. We determined the expression of seven genes proximally located at the selected differentially methylated regions. Expression levels of WDR27, GNAS, DOK7, MCF2L, PRKG1, and CMYA5 were significantly different between control vs OA and OA vs treatment with food components. We demonstrated that DNA methylation was associated with expression of genes in the model of hepatic steatosis. We also found that food components reversely changed DNA methylation induced by OA and alleviated lipid accumulation. These results suggest that DNA methylation is one of the mechanisms causing the hepatic steatosis and its regulation by food components provides insights that may prevent or alleviate lipid accumulation.